تأثير تحول صراع المهمة إلى صراع علاقة في الالتزام التنظيمي لأعضاء الهيئة التدريسية في جامعة تشرين (Latakia University Journal - Economic and Legal Sciences Series, 2018)
This study discusses the effect of turning the task conflict into a  relationship Conflict in the organizational commitment, of the academic staff at Tishreen University, and therefore This research aims to determine the degree of the effect of turning the task conflict into a relationship conflict in the organizational level of commitment, and the researcher depends on the descriptive and analytical approach in conducting research . The sample consisted of search (240) academic staff at Tishreen University. The research found the following results: • The existence of significant influence to transform the task conflict into a relationship conflict  in both emotional and normative commitment of the academic staff at Tishreen University. Where it was an inverse relationship medium, that is, transforming the task conflict, to  relationship conflict, leads the low level of both emotional and normative commitment.• The existence of significant influence of  transforming the task conflict into a relationship conflict  in the ongoing commitment of the academic staff at Tishreen University. Where it was a positive relationship is weak, that is, the increasing turning task conflict into a relationship conflict leads to increased organizational commitment. تتناول هذه الدراسة تأثير تحول صراع المهمة إلى صراع علاقة في الالتزام التنظيمي لدى أعضاء الهيئة التدريسية في جامعة تشرين، وبناءً عليه يهدف هذا البحث إلى تحديد درجة تأثير تحول صراع المهمة إلى صراع علاقة في مستوى الالتزام التنظيمي ، واعتمد الباحث على المنهج الوصفي التحليلي في إجراء البحث. وتكونت عينة البحث من (240) عضو هيئة تدريسية في جامعة تشرين. وتوصل البحث إلى النتائج الآتية: ·وجود تأثير جوهري لتحول صراع المهمة إلى صراع علاقة في كل من الالتزام العاطفي  والمعياري لأعضاء الهيئة  التدريسية في جامعة تشرين. حيث كانت العلاقة عكسية متوسطة، أي أنّ تحول صراع المهمة إلى صراع علاقة يؤدي انخفاض مستوى كل من الالتزام العاطفي والمعياري. ·وجود تأثير جوهري  لتحول صراع المهمة إلى صراع علاقة في الالتزام المستمر لأعضاء الهيئة  التدريسية في جامعة تشرين. حيث كانت العلاقة طردية ضعيفة، أي أنَّ ازدياد تحول صراع المهمة إلى صراع علاقة يؤدي إلى ازدياد الالتزام التنظيمي.